Laser assisted tooling in metal forming - Kreis, Oliver; Geiger, Manfred; Vahl, Meik (Proceedings of the 2nd International Conference on Industrial Tools (ICIT), 1999)
This article describes several applications of laser technology for tooling. Laminated tools and laser sintering as technologies for rapid tooling are presented. In the field of laser beam surface treatment, the technologies laser ablating, hardening and microstructuring are discussed. Finally, the integration of cutting and laser beam welding in the tool of a forming press is described.</
Keywords: Rapid Tooling; Laminated Tools; Laser Sintering; Laser Surface Treatment; Hydroforming; Process Integration